A new type of Anatolian propolis: Evaluation of its chemical composition, activity profile and botanical origin - Değirmencioğlu, Hacer Tuğba; Güzelmeriç, Etil; Yüksel, Parla Işıl; Kırmızıbekmez, Hasan; Deniz, İnci; Yeşilada, Erdem (Wiley, 2019)
This study was undertaken to analyze the phenolic profiles of 19 propolis samples from Turkey by using a high-performance thin-layer chromatographic (HPTLC) method in order to identify their plant origins. Furthermore, their antioxidant and antimicrobial activity profiles were comparatively evaluated. For the appraisal of antioxidant potential, total phenolic (TPC) and total flavonoid contents (TFC) of propolis samples were firstly determined and then their effects on free radicals were evaluated by FRAP, ABTS(.+), CUPRAC, DPPH. and HPTLC-DPPH. methods. Antimicrobial activity of propolis samples against Staphylococcus aureus (ATCC 6538), Pseudomonas aeruginosa (ATCC 15442), Escherichia coli (ATCC 11229) and Candida albicans ATCC 10231 were determined by disc diffusion and broth dilution methods. HPTLC fingerprinting analyses revealed that O-type (botanical origin from Populus nigra L.) was the primarily available propolis type in Turkey. Moreover, 3-O-methylquercetin (3MQ) rich propolis was identified as a new propolis type for the first time. Principal component analysis (PCA) indicated that 3MQ-type propolis differs from the O-type. Antioxidant activity studies showed that O-type of propolis possesses higher antioxidant effect than the other tested propolis types. Quercetin, caffeic acid, caffeic acid phenethyl ester (CAPE) and galangin were determined to contribute significantly to the antioxidant potential of O-type propolis among others. Propolis extracts exerted moderate antimicrobial activity against the tested microorganisms with MIC values between the ranges of 128-512 mu g/mL.
Keywords: Propolis; High-Performance Thin-Layer Chromatography (HPTLC); Antimicrobial Activity; Principal Component Analysis